Analisis Filsafat Ilmu Pengetahuan dalam Transformasi Digital Tridharma Perguruan Tinggi Menuju Smart Campus: An Analysis of the Philosophy of Science in Digital Transformation The Tridharma of Higher Education Towards a Smart Campus - Johan, Meliana Christianti; Langi, Armein Z. R.; Mahayana, Dimitri; Abbas, Muhammad Fadhl (Undiksha, 2025)
The technological revolution has driven the digital transformation of higher education institutions towards a Smart Campus. This process often focuses on technical aspects and neglects philosophical foundations, risking unsustainable implementation. This study analyzes digital transformation in the Tridharma of Higher Education using a philosophy of science approach. It applies interpretive qualitative content analysis to 10 Q1 journal articles from 2021 to 2024. The analysis reveals three fundamental findings. Ontologically, technology is not a neutral tool, but an active agent that shapes academic reality. Epistemologically, there is a dilemma between personalization and standardization of knowledge and the challenge of academic integrity due to Generative AI. Axiologically, operational efficiency can conflict with the humanization of education, as well as innovation and data privacy. This research produces a value-based strategic framework of eight pillars: human-centered design, ethics from the outset, pedagogical accuracy, equity and inclusion, cultural responsiveness, sustainability, governance, and capacity building. This framework guides the implementation of an ethical and sustainable Smart Campus in Indonesia, aligning with the values of Tridharma.